2014
DOI: 10.1016/j.jebo.2014.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Optimal prizes in dynamic elimination contests: Theory and experimental evidence

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Schmidt et al (2011) also find that the single-prize contest results in a higher aggregate effort than the multiple-prize contest, although their theoretical model predicts that under risk neutrality both contests are equivalent. Stracke et al (2012) show that even in a multi-stage elimination lottery contest between symmetric players, a single-prize generates higher efforts than when multiple prizes are allocated at the end of the contest. Multiple prizes also perform poorly in rank-order tournaments, as confirmed by Orrison et al (2004), who find that total effort is lower in tournaments with many small prizes than with few large prizes.…”
Section: Multiple Prizesmentioning
confidence: 92%
“…Schmidt et al (2011) also find that the single-prize contest results in a higher aggregate effort than the multiple-prize contest, although their theoretical model predicts that under risk neutrality both contests are equivalent. Stracke et al (2012) show that even in a multi-stage elimination lottery contest between symmetric players, a single-prize generates higher efforts than when multiple prizes are allocated at the end of the contest. Multiple prizes also perform poorly in rank-order tournaments, as confirmed by Orrison et al (2004), who find that total effort is lower in tournaments with many small prizes than with few large prizes.…”
Section: Multiple Prizesmentioning
confidence: 92%
“…There is a growing number of experimental studies investigating the optimality of the prize structure in contests (Harbring and Irlenbusch, 2003;Orrison et al, 2004;Müller and Schotter, 2010;Chen et al, 2011;Sheremeta, 2011a;Shupp et al, 2013;Lim et al, 2014;Stracke et al, 2014). These studies are based on different theoretical models (i.e., lottery contests, all-pay auctions and rank-order tournaments), and thus they are not directly comparable.…”
Section: Multiple Prizesmentioning
confidence: 99%
“…Therefore, when there are multiple upward comparisons, given the same prize size, the performance incentive is larger in the first stage. Stracke et al () showed that compared with a winner‐takes‐all tournament, a tournament that allocates more prizes to first‐round winners results in a higher effort level in the first round. To our knowledge, no study has applied multistage tournament theory in the corporate context.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Second, our study is related to and adds to the labour economics literature that uses experiments to study the incentive effect of different prize structures in a tournament setting (Altmann, Falk, & Wibral, 2012;Delfgaauw, Dur, Non, & Verbeke, 2015;Freeman & Gelber, 2010;Sheremeta, 2010;Stracke, Höchtl, Kerschbamer, & Sunde, 2014). It is most closely related to Freeman and Gelber (2010), which examined prize spread (i.e., pay gap) and the performance of experimental participants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation